2018
DOI: 10.1155/2018/3058241
|View full text |Cite
|
Sign up to set email alerts
|

A Cellular Automata-Based Simulation Tool for Real Fire Accident Prevention

Abstract: Many serious real-life problems could be simulated using cellular automata theory. There were a lot of fires in public places which kill many people. Proposed method, called Cellular Automata Evaluation (CAEva in short), is using cellular automata theory and could be used for checking buildings conditions for fire accident. The tests performed on real accident showed that an appropriately configured program allows obtaining a realistic simulation of human evacuation. The authors analyze some real accidents and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…For the needs of the first stage of the research, the most frequent functions were selected. Six commonly known mathematical functions were selected - [Abbass 2003…”
Section: Organization and Course Of Researchmentioning
confidence: 99%
“…For the needs of the first stage of the research, the most frequent functions were selected. Six commonly known mathematical functions were selected - [Abbass 2003…”
Section: Organization and Course Of Researchmentioning
confidence: 99%
“…In the literature, most attention is dedicated to the issue of the similarity of objects (Stachowiak andDyczkowski 2013, Wenyi et al 2016). In recent decades, the theory of fuzzy sets has been used in many areas of science and everyday life (Czerniak et al 2017a, Zarzycki et al 2017a, Ewald 2018a, Apiecionek et al 2018, Marszałek 2014. The need to compare fuzzy sets emerged naturally from the very beginning of the theory.…”
Section: Intruductionmentioning
confidence: 99%
“…Calculation of the R value using the Mandala Factor for the rising edge, falling edge and core set function integral. Then the obtained value should be scaled from the center of the coordinate system by adding it to the start of the support value of the fuzzy number (Czerniak et al, 2018). When defuzzyfication is performed in the OFN arithmetic, then in the case of a positive order, one should proceed as described below, while in the case of a negative order, one should deduct the calculated value from the first coordinate of the OFN number corresponding to the outermost right side of the OFN support.…”
Section: Mandala Factor (Ml) Defuzzyfication Operatormentioning
confidence: 99%
“…Facing emergencies such as hurricanes, tsunamis, fires, and poisonous gas leakage [1], some methods were proposed to find the optimal path according to the prior information [2,3], and the methods are not suitable for the emergency evacuation when the situations are significantly different from the prior information. Studies have shown that fire is the most frequent accident among the above emergencies [4][5][6], and it gets more attention from researchers since fire accidents frequently cause huge losses to mankind; then, this paper takes fire accident as an example to introduce the proposed algorithm principle. e evacuation environment includes route topology, exit location, evacuee size, and people distribution, and changes of each element bring different evacuation paths.…”
Section: Introductionmentioning
confidence: 99%